Cotinine Analysis in Active Smoker's Urine by Immunochromatography Assay Method - Fery Eko Pujiono; Putri Solikah; Tri Ana Mulyati (Jurnal Sintesis: Penelitian Sains, Terapan dan Analisisnya, 2022)
Cigarettes are the main product of tobacco processing. Cotinine is often used as a biomarker in the assessment of nicotine exposure because it has a half-life of 15-20 hours in the blood. This compound is easily detected in saliva, urine and blood. Cotinine in urine can be detected using an immunochromatography assay. The purpose of this study was to describe the results of cotinine examination in the urine of active smokers using the immunochromatography assay method in Sumuragung Village, Bojonegoro. This study used a descriptive research design that collected 26 smokers in the village of Sumuragung Bojonegoro who were selected using a purposive sampling technique. A total of 26 urine samples were detected using the immunochromatography assay method. The results of cotinine examination in the urine of active smokers showed that there were 25 people (96%) positive and 1 person (4%) negative. Based on the results of the study, it can be concluded that the urine of active smokers contains cotinine.